Electrical Stimulation and Swallowing: How Much Do We Know? - Humbert, Ianessa A.; Michou, Emilia; MacRae, Phoebe R.; Crujido, Lisa (Seminars in Speech and Language, 2012)
Consequences of dysphagia substantially reduce quality of life, increase the risk of medical complications and mortality, and pose a substantial cost to healthcare systems. As a result, it is of no wonder that the clinical and scientific communities are showing interest in new avenues for dysphagia rehabilitation. Electrical stimulation (e-stim) for the treatment of swallowing impairments is among the most studied swallowing interventions in the published literature, yet many unanswered questions about its efficacy remain. In the meantime, many speech-language pathologists who treat dysphagia are attending educational and training sessions to obtain certifications to use this technique. Here, we review the values and limitations of the published literature on the topic of e-stim for swallowing to assist clinicians in decision making in their clinical practice. The discussion provides a review of swallowing anatomy and physiology, the fundamentals of e-stim, and information essential for the readers' independent critique of these studies—all of which are crucial for evaluating the possible effects of e-stim.
Keywords: Deglutition disorders; electrical stimulation